NAVIGATING ACADEMIC SUCCESS: UNDERSTANDING THE IMPACT OF STRESS COPING STRATEGIES ON ADOLESCENT MALE STUDENTS IN SENIOR SECONDARY SCHOOLS (International Journal of Food and Nutritional Sciences, 2022)
The objective of this research was to assess the impact of various coping strategies on the academic achievement of senior secondary school students. The sample consists of one hundred class XII male senior secondary school students. Jaipur, the capital city of Rajasthan, was the study area. The assessment of coping strategies in the chosen participants was conducted using the Coping Strategies Scale, which was developed by Srivastava in 2001. The evaluation of coping strategies in this study includes five distinct approaches: behavioural approach, cognitive approach, cognitive-behavioural approach, behavioural avoidance, and cognitive avoidance. The academic achievement of male adolescents in class XII was assessed based on their academic achievements in the preceding year. The correlation between coping strategies and academic achievement was found to be significant and positive in the context of behavioural, cognitive, and cognitive behavioural approaches. In contrast, the relationship between behaviour avoidance and cognitive avoidance coping strategies and academic achievement was significant but negative. The study concluded that stress coping strategies, particularly the behavioural, cognitive, and cognitive behavioural approaches, prove to be more effective in enhancing the academic achievement of adolescent male class XII students compared to the behavioural and cognitive avoidance coping strategies.